2002
DOI: 10.1080/09540120208629671
|View full text |Cite
|
Sign up to set email alerts
|

Chatters on the Internet: a special target group for HIV prevention

Abstract: This study examined characteristics of men who use gay chat boxes on the Internet, including dating behaviour and sexual risk-taking with sex partners who were initially met through chatting. Men on chat boxes were asked to complete a brief questionnaire on the Internet. The questionnaire contained questions on demographics, chatting-related variables, and dating and risk-taking sexual behaviour. The results show that a large majority of the 190 respondents reported actual encounters as well as sex with men wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 6 publications
4
37
0
Order By: Relevance
“…A Netherlands study found that a safer sex website, an email-based question and answer program, and a safe sex chat room were the most preferred programs. 9 Men online in the UK also had favorable attitudes towards online health promotion. 33 In fact, most men (75%) thought that Internet sites should allow health workers into chat rooms, would click on a banner to find out about sexual health (78%), and were agreeable to engaging health workers online (84%).…”
Section: Outreach and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Netherlands study found that a safer sex website, an email-based question and answer program, and a safe sex chat room were the most preferred programs. 9 Men online in the UK also had favorable attitudes towards online health promotion. 33 In fact, most men (75%) thought that Internet sites should allow health workers into chat rooms, would click on a banner to find out about sexual health (78%), and were agreeable to engaging health workers online (84%).…”
Section: Outreach and Preventionmentioning
confidence: 99%
“…Not surprisingly, many individuals have turned to the Internet to seek love, companionship, and sex. 1,2 Men who have sex with men (MSM) are avid users of the Internet for dating and sexual purposes, as documented both by the number of studies [3][4][5][6][7][8][9][10][11][12][13][14][15] and the increasing number of Internet services catering to MSM. Mainstream Internet providers, such as America OnLine (AOL), feature user-created chat rooms where MSM can easily find each other in rooms labeled, for instance, Bm4m^and coded by geographical location (e.g., NYCm4m), HIV status (e.g., HIVm4m), ethnicity (e.g., Latinom4m), or more arcane names known only to the initiated [e.g., BAtlantabimm4bimm^(for bisexual married men)].…”
Section: Introductionmentioning
confidence: 99%
“…Current estimates indicate that MSM are 7 times more likely to have sex with Internet partners than non-MSM (Bull, McFarlane, & Rietmeijer, 2001). Perhaps of even greater significance, MSM who use the Internet to look for sexual partners are more likely than those who do not to engage in unprotected sex (Benotsch, Kalichman, & Cage, 2002;Hospers, Harterink, van den Hoek, & Veenstra, 2002;Liau et al, 2006). Hospers et al (2002) reported that 30% of the MSM in their sample who engaged in sex with men they met on the Internet reported inconsistent safe sexual behaviors.…”
Section: Risks Of Using the Internet To Recruit Bareback Sexual Partnersmentioning
confidence: 99%
“…Next, it is essential that practitioners question their clients about the use of the Internet to meet sexual partners. Research indicates that MSM who meet sexual partners on the Internet are less likely to use consistent safer sex practices (Benotsch et al, 2002;Hospers et al, 2002;Liau et al, 2006). Thus, clinicians should attempt to educate clients about the importance of consistent condom use among sex partners, regardless of where these partners initially meet.…”
Section: Implications For Education and Researchmentioning
confidence: 99%
“…The majority of these studies found associations between having met sex partners online and rates of high-risk sexual behavior (Bolding, Davis, Hart, Sherr, & Elford, 2005;Hirshfield, Remien, Humberstone, Walavalkar, & Chiasson, 2004;Hospers, Harterink, Van Den Hoek, & Veenstra, 2002). Additional studies have shown that men who use the Internet to meet male sex partners may also engage in more high-risk behaviors than those who do not (Benotsch et al, 2002;Kim, Kent, McFarland, & Klausner, 2001;Liau, Millet, & Marks, 2006;Whittier, Seeley, & St. Lawrence, 2004).…”
mentioning
confidence: 99%